Involvement of the C‐terminal domain in cell surface localization and G‐protein coupling of mGluR6. Issue 4 (31st October 2020) - Rai, Dilip; Akagi, Takumi; Shimohata, Atsushi; Ishii, Toshiyuki; Gangi, Mie; Maruyama, Takuma; Wada‐Kiyama, Yuko; Ogiwara, Ikuo; Kaneda, Makoto
Abstract: Metabotropic glutamate receptor 6, mGluR6, interacts with scaffold proteins and Gβγ subunits via its intracellular C‐terminal domain (CTD). The mGluR6 pathway is critically involved in the retinal processing of visual signals. We herein investigated whether the CTD (residues 840–871) was necessary for mGluR6 cell surface localization and G‐protein coupling using mGluR6‐CTD mutants with immunocytochemistry, surface biotinylation assays, and electrophysiological approaches. We used 293T cells and primary hippocampal neurons as model systems. We examined C‐terminally truncated mGluR6 and showed that the removal of up to residue 858 did not affect surface localization or glutamate‐induced G‐protein‐mediated responses, whereas a 15‐amino acid deletion (Δ857‐871) impaired these functions. However, a 21‐amino acid deletion (Δ851‐871) restored surface localization and glutamate‐dependent responses, which were again attenuated when the entire CTD was removed. The sequence alignment of group III mGluRs showed conserved amino acids resembling an ER retention motif in the CTD. These results suggest that the intracellular CTD is required for the cell surface transportation and receptor function of mGluR6, whereas it may contain regulatory elements for intracellular trafficking and signaling. Abstract : The intracellular C‐terminal domain (CTD) of G‐protein‐coupled receptors generally interacts with PDZ domain‐containing scaffold proteins and Gβγ subunits. We herein investigated whether mGluR6 CTD contributes to receptor cell surface localization and G‐protein coupling. Using 293T cells and hippocampal neuron cultures, we demonstrate that the deletions of the distal half of CTD attenuated mGluR6 surface localization and G‐protein coupling. However, these functions were restored by further deletions of the distal two‐thirds encoding an RXR‐type ER retention motif, which may be masked by the distal half of CTD. The results provide insights into the mechanisms underlying intracellular trafficking and signaling of mGluR6.